2014
DOI: 10.1002/ajmg.a.36815
|View full text |Cite
|
Sign up to set email alerts
|

Complex de novo chromosomal rearrangement at 15q11–q13 involving an intrachromosomal triplication in a patient with a severe neuropsychological phenotype: Clinical report and review of the literature

Abstract: Interstitial triplications of 15q11-q13, leading to tetrasomy of the involved region, are very rare, with only 11 cases reported to date. Their pathogenicity is independent of the parental origin of the rearranged chromosome. The associated phenotype resembles, but is less severe, than that of patients bearing inv dup(15) marker chromosomes. Here, we describe a boy of 3 years and 9 months of age who exhibited very mild craniofacial dysmorphism (arched eyebrows, hypertelorism, and a wide mouth), developmental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 24 publications
1
21
1
Order By: Relevance
“…In the processed cohort, we found that 20% of CNVs were associated to a known syndrome, a value lower than the one obtained for the CNVs identified by CMA studies (Ahn et al, ; Castronovo et al, ; Kaminsky et al, ; Mc Cormack et al, ). In compliance with the literature, the most common microdeletion syndromes are the 22q11.2 and the 16p11.2 microdeletion, while the most common microduplication syndromes are the 15q11.2, the 16p13.11, and the 16p11.2 microduplications (Ahn et al, ; Kaminsky et al, ).…”
Section: Discussioncontrasting
confidence: 73%
“…In the processed cohort, we found that 20% of CNVs were associated to a known syndrome, a value lower than the one obtained for the CNVs identified by CMA studies (Ahn et al, ; Castronovo et al, ; Kaminsky et al, ; Mc Cormack et al, ). In compliance with the literature, the most common microdeletion syndromes are the 22q11.2 and the 16p11.2 microdeletion, while the most common microduplication syndromes are the 15q11.2, the 16p13.11, and the 16p11.2 microduplications (Ahn et al, ; Kaminsky et al, ).…”
Section: Discussioncontrasting
confidence: 73%
“…Prior to WES, 42 patients took one or more genetic tests (33 patients underwent karyotype analysis, 10 microarray analysis, and 13 took another genetic test such as mutation screening for a few epilepsy genes). 15q11-q13 interstitial triplication (Case732), 19 Terminal 14q deletion syndrome (Case 741), 20 Pelizaeus-Merzbacher disease (Case 751), 21 Potocki-Lupski syndrome (Case 760), 22 1p36 deletion syndrome (Case 811), 23 Williams-Beuren syndrome (Case 815), 24 1q44 deletion syndrome (Case 919), 25 and 1q43-q44 deletion syndrome (Case 944). 26 35 and FOXG1 (Case 995).…”
Section: Overview Of the Studied Familiesmentioning
confidence: 99%
“…It's reported that people with 15q11-q13 dup syndrome or inv dup (15) are pathogenic only when the extra parts inherited form mother, and the level of effect on brain function and development have much to do with the maternal gene dosage [25,26]. Though CNV-Seq can be used in detecting dup15q syndrome accurately, but it cann't determine whether the extra fragment is paternal or maternal without other technologies such as FISH or quantitative fluorescent polymerase chain reaction (QF-PCR).…”
Section: Discussionmentioning
confidence: 99%